PENGARUH PEMBERIAN AROMATERAPI KAYU MANIS TERHADAP DERAJAT DISMENORE PADA USIA REMAJA DI DESA SUKAMANTRI TANGERANG - Fatmawati, Siti; Kamil, Ikhsan; Ratnasari, Febi (Nusantara Hasana Journal, 2021)
Dysmenorrhea is a common cause of absence of someone in the office and school to go to the doctor, which causes a decrease in performance at work and study. Although dysmenorrhea is not life threatening, this can have an effect on the quality of life, adolescent activities can be disrupted due to dysmenorrhea so that they cannot carry out activities, this can interfere with adolescent learning activities at school. The purpose of this study was to determine the effect of giving cinnamon aromatherapy to adolescents. Using quantitative methods with pre-experimental research design, the population in the study amounted to 150 adolescents aged (15-21 years) and 30 respondents who experienced dysmenorrhea or menstrual pain in Sukamantri Village, Tangerang. The sampling technique was a purposive method. The instrument used is a questionnaire sheet and the provision of intervention. The results of the study analyzed the average value of the data, namely, the pretest was 3,3667%, while the posttest experienced a decrease in the average value, namely 1,9667%. This means that it can influence giving cinnamon aromatherapy to adolescents who experience dysmenorrhea.